2018
DOI: 10.1097/mpg.0000000000001849
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Appetite Manipulation in Children with Feeding Disorders Admitted to an Inpatient Feeding Program

Abstract: Adverse effects are common when appetite manipulation is used to wean children off G-tube dependence. Anticipating, monitoring, and having a clear intervention plan in a closely monitored setting are necessary to safely use this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Across the included studies, we identified 3 distinct approaches to intervention with the ultimate aim of tube weaning: (1) those grounded in behavioral strategies, 7–12,20,21,28,34,35,40 (2) those with a biomedical or other treatment focus, 17,27,39,41 and (3) those that followed a child‐ and family‐centered approach 13–16,18,19,22,24–26,29,36,37,42,43 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the included studies, we identified 3 distinct approaches to intervention with the ultimate aim of tube weaning: (1) those grounded in behavioral strategies, 7–12,20,21,28,34,35,40 (2) those with a biomedical or other treatment focus, 17,27,39,41 and (3) those that followed a child‐ and family‐centered approach 13–16,18,19,22,24–26,29,36,37,42,43 …”
Section: Resultsmentioning
confidence: 99%
“…Most (n = 11) but not all behavioral approaches used a combination of hunger induction and tube‐feed reduction only when oral intake reached a predetermined level. This approach to feeding therapy was most frequently reported by studies describing programs in North America (11 programs), 7–12,20,21,28,35,40 by 1 paper from the Netherlands, 34 and by 1 from New Zealand 38 . Behavioral approaches represent the earliest published modes of teaching tube‐dependent children to eat 12 and continue to be used 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients undergoing this weaning approach achieved complete or substantial weaning from their G-tube treatment, but adverse effects persisted in others. Adverse effects such as ketonuria and hypoglycemia should be monitored in patients during the appetite manipulation process as this period of induced acute starvation may lead to appetite suppression [60,62]. A combined approach is further supported in a 2014 study by Brown et.…”
Section: The Weaning Processmentioning
confidence: 97%
“…Children were evaluated for oral feeding readiness and underwent appetite manipulation through gradual restriction leading to the eventual elimination of G-tube treatment. This approach optimized the children's hunger response and addressed potential disruption of the hunger cycle generated from the G-tube feeding [60,61]. The majority of patients undergoing this weaning approach achieved complete or substantial weaning from their G-tube treatment, but adverse effects persisted in others.…”
Section: The Weaning Processmentioning
confidence: 99%